Agronomic, physiological and molecular characterization of spring wheat (Triticum aestivum L.) accessions for drought tolerance (Bangladesh Journal of Botany, 2020)
A comprehensive study was conducted to investigate (i) the effect of drought stress on genetic association among various yield traits and (ii) molecular and phenotypic diversity in the selected spring wheat accessions. A panel of 24 spring wheat accessions was evaluated under normal irrigation and drought stress. Data were collected for chlorophyll contents, canopy temperature, days to heading, grain filling period, relative water content, plant height, peduncle length, number of kernels per spike, 1000-kernel weight and grain yield. Analysis of variance depicted significant differences for genotypes (G), effect of treatment (T) and interaction between T and G. Correlation analysis revealed that genetic association among various traits was stronger in normal treatment than water stressed. The Biplot analysis grouped the genotypes into tolerant and susceptible groups. Molecular characterization of tolerant and susceptible genotypes was done with 14 ISSR markers. ISSR primers revealed a mean of 0.63 genetic similarities among genotypes. Polymorphism information content (PIC) values varied from 0.24 to 0.49. The genetic diversity in selected germplasm can be used to develop drought tolerant lines considering the changing pattern of traits association under drought stress.